Electrocardiography changes in localizing the culprit vessel in acute myocardial infarction with angiographic correlations - Sampath, Senthil Kumar; Sivasubramanian, Vithiavathi; Lakshminarayanan, Satish (International Journal of Advances in Medicine, 2019)
Background: The electrocardiogram is the primary diagnostic tool to evaluate a patient with chest pain and suspected myocardial infarction. Anterior wall infarction due to occlusion of proximal LAD has worse prognosis compared to distal or branch vessel lesions. Diagnosis of anterior/inferior/posterior or lateral MI is based on patterns of ST deviation and risk assessment based on absolute magnitude of ST segment deviation or the width of QRS complexes. Although coronary angiography is the gold standard for determining the infarct related artery in acute myocardial infarction, ECG can be useful tool in identifying the culprit artery involved at the primary care. Methods: A prospective cross-sectional study was conducted in Aarupadai Veedu Medical College and Hospital. Standard 12 lead electrocardiograph were recorded for 50 patients at a speed of 25 mm/s and voltage of 10mm/mv. Patients who had acute inferior wall MI additional right pericardial leads were recorded (V3R and V4R). The recorded ECG was interpreted using the electrocardiographic algorithms of Zimet-baum PJ et al. An ST elevation or depression was considered significant only if it was >1mm. Results: The study result showed maximum specificity for LCx (100%) followed by RCA (92.67) and LAD (89.91). The sensitivity for identifying the culprit artery by ECG in acute myocardial infarction was 100% for both LAD and RCA coronary artery but 0% for LCx coronary artery. In case of LAD occlusion, the sensitivity is 100% for proximal LAD occlusion and 92.86%for distal LAD occlusion. The sensitivity and specificity for proximal and distal RCA is 100% and 80.43% respectively. Conclusions: ECG is an easily, widely available and non-invasive tool to localize the site of culprit artery in acute myocardial infarction.